Surgical Treatment for Scoliosis - Tjokorda Gde Bagus Mahadewa (Neurologico Spinale Medico Chirurgico, 2018)
Recently, patients with spinal deformities, particularly scoliosis, could be handled well through surgical pathways. Generally, surgery is indicated in patients with scoliosis curve exceeding 45 degrees (COBB angle > 45). The ultimate goal is to reduce the curve as optimally as possible without disturbing spinal cord. Whether the result is straight or not, it also depends on the patient's spine flexibility before surgery. Surgical indications are for improving appearance, preventing increasing degrees of the curve, preventing interference to other organs such as the lungs, and preventing neurological deficits. Correction of Cobb angle below 25 degrees had already makes the patient feel more comfortable. The amount of screw and instrumentation length depends on the number of spines involved. After surgery treatment, 2-4 weeks of rest are required before returning to daily activity. Fusion principle states that the spine will be slightly stiff in order to be corrected but it is believed that patient's activity could still be done with the remaining flexibility. Surgical treatment of scoliosis that does meet the indications is imperative and relatively safe with advances in medical technology today.